Context of Situation in Students’ Textbook: A Pragmatic Study - Santosa, Aulia Wahyu; Fauziati, Endang; Supriyadi, Slamet (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This research study is a pragmatic analysis which focuses on context of situation in English Textbook. The objective of the study is to describe the four components of context of situation in the dialogues contains in the textbook. This research applies descriptive qualitative type. By applying this method, the researcher uses the dialogues in one unit of textbook as the data source, while the data of the research are the elaboration of each component of the dialogues. The result of the research show that although there are some components of context of situation that is stated implicitly or even unclear, the ideas of the dialogue are still can be understood.